2016
DOI: 10.3389/feart.2016.00074
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Leaching from Tropical Peat Soils and Consequences for Carbon Balances

Abstract: Drainage and deforestation turned Southeast (SE) Asian peat soils into a globally important CO 2 source, because both processes accelerate peat decomposition. Carbon losses through soil leaching have so far not been quantified and the underlying processes have hardly been studied. In this study, we use results derived from nine expeditions to six Sumatran rivers and a mixing model to determine leaching processes in tropical peat soils, which are heavily disturbed by drainage and deforestation. Here we show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 25 publications
3
33
0
Order By: Relevance
“…Previous research on the effects of peat swamp forest disturbance has predominately focused on direct atmospheric GHG emissions from the peat surface (Couwenberg et al, 2010;Hooijer et al, 2010;Page et al, 2011;Hirano et al, 2012;Matysek et al, 2017). Until fairly recently, fluvial carbon losses received less attention, but more recent data suggest that this flux can represent a substantial fraction of the tropical peatland carbon balance (Moore et al, 2013;Evans et al, 2014;Rixen et al, 2016;Yupi et al, 2017). Fluvial total organic carbon (TOC) is typically dominated by dissolved organic carbon (DOC), with particulate organic car-bon (POC) contributing < 10 % of the total flux (Moore et al, 2013;Yupi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on the effects of peat swamp forest disturbance has predominately focused on direct atmospheric GHG emissions from the peat surface (Couwenberg et al, 2010;Hooijer et al, 2010;Page et al, 2011;Hirano et al, 2012;Matysek et al, 2017). Until fairly recently, fluvial carbon losses received less attention, but more recent data suggest that this flux can represent a substantial fraction of the tropical peatland carbon balance (Moore et al, 2013;Evans et al, 2014;Rixen et al, 2016;Yupi et al, 2017). Fluvial total organic carbon (TOC) is typically dominated by dissolved organic carbon (DOC), with particulate organic car-bon (POC) contributing < 10 % of the total flux (Moore et al, 2013;Yupi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previous attempts to quantify fluvial carbon losses from tropical peatlands include Moore et al (2013), Gandois et al (2013), Wit et al (2015), Rixen et al (2016), and Yupi et al (2016). Moore et al (2013) reported that losses of DOC from disturbed tropical peatlands in Indonesia were around 50 % greater than those from an adjacent intact peat swamp forest.…”
Section: Introductionmentioning
confidence: 99%
“…In peat dominated ecosystems such as the Páramo, changes in rainfall and temperature fluctuations as well as LC/LU changes are directly and strongly related to soil carbon losses (Freeman, Evans, & Monteith, 2001;Rixen, Baum, Wit, & Samiaji, 2016). The impact of a number of climatic and LC/LU related factors (e.g., temperature increase, deforestation, or droughts), which influence dissolved organic carbon (DOC) mobilization, has already been observed in other ecosystems in temperate regions (Borken, Ahrens, Schulz, & Zimmermann, 2011;Freeman et al, 2001;Laine, Strömmer, & Arvola, 2014;Sarkkola et al, 2009;Stutter, Langan, & Cooper, 2008).…”
mentioning
confidence: 99%
“…However, during rising tide in Sarikei, we observed pCO 2 values of almost 6000 µatm, which is higher than the freshwater end-member, suggesting that other effects also play a role. Among those are decomposition of organic matter in intertidal sediments (Alongi et al, 1999;Cai et al, 1999) and subsequent transport of the produced CO 2 to the river, as well as groundwater input (Rosentreter et al, 2018).…”
Section: Impact Of the Peatlands On The Co 2 Emissions From The Rajanmentioning
confidence: 99%